Jaynes-Cummings theory out of the box - Groves, Elizabeth; Clader, B D; Eberly, J H (Journal of physics. B, Atomic, molecular, and optical physics, 2013)
We report new results in neoclassical quantum optics by applying the central theme of the Jaynes-Cummings paper of 1963. This theme, which Jaynes and Cummings emphasized in several ways, is the key role that must be assigned to radiative back reaction in quantum radiation dynamics. Its consequences are well known in subjects related to cavity quantum electrodynamics, and its influence on optical pulse evolution theory is equally strong. Here we provide a new solitonic extension of the radiation reaction theme to short-pulse broad-bandwidth propagation theory. We report a single formula encapsulating a three-pulse scenario in which the stable imprint of signal-pulse coherence, placed in an atomic medium at a predictable location by an initial pulse pair, is subsequently transferred by a third pulse to a different location. This is analysed by reference to our new analytic solution of the nonlinearly coupled density matrix equations that incorporate the radiation reaction fields obtained from the Maxwell equations for the pulses in the atomic medium.